2009
DOI: 10.1111/j.1365-2443.2008.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel REV1‐interacting motif necessary for DNA polymerase κ function

Abstract: When a replicative DNA polymerase (Pol) is stalled by damaged DNA, a 'polymerase switch' recruits specialized translesion synthesis (TLS) DNA polymerase(s) to sites of damage. Mammalian cells have several TLS DNA polymerases, including the four Y-family enzymes (Polη, Polι, Polκ and REV1) that share multiple primary sequence motifs, but show preferential bypass of different DNA lesions. REV1 interacts with Polη, Polι, and Polκ and therefore appears to play a central role during TLS in vivo. Here we have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
191
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(208 citation statements)
references
References 29 publications
13
191
3
1
Order By: Relevance
“…As shown in Fig. 5B, Polk ) ⁄ ) cells showed mild sensitivity to UV irradiation, as previously reported (Ogi et al 2002;Ohashi et al 2009), and…”
Section: Inactive Polg Partially Restored Uv Sensitivitysupporting
confidence: 64%
“…As shown in Fig. 5B, Polk ) ⁄ ) cells showed mild sensitivity to UV irradiation, as previously reported (Ogi et al 2002;Ohashi et al 2009), and…”
Section: Inactive Polg Partially Restored Uv Sensitivitysupporting
confidence: 64%
“…3C). Because these two Pol residues are not conserved and their alanine substitutions do not affect the Rev1 CTD-Pol RIR binding affinity (17), their crystallographically observed polar interactions may not contribute significantly to the binding energy.…”
Section: Formation Of a Quaternary Translesion Polymerase Complexmentioning
confidence: 99%
“…Rev1 interaction is required for the protective role of Pol against benzo[a]pyrene in mammalian cells, and it promotes Pol -mediated suppression of spontaneous mutations in human cells (17,18). Although the interactions between the Rev1 CTD and the RIRs of Y-family polymerases , , and are only found in vertebrates (15), the Rev1 CTD-Pol interaction is evolutionarily conserved from yeast to humans, highlighting the essential role of the Rev1-Pol interaction in translesion synthesis.…”
mentioning
confidence: 99%
“…Based on these findings, it was proposed that REV1 acts as a scaffold protein to coordinate TLS polymerase switching (10,14,28,43,58). To support this notion, recent studies have indicated that the REV1/Pol interaction is required for Pol function (41) and that the REV1/Pol interaction promotes targeting of REV1 to UV-damaged DNA (1).Among the Y-Pols, REV1 and Pol are conserved throughout the eukaryotes and have been extensively studied. Substantial evidence indicates that posttranslational control of Pol plays an important role in the regulation of its function.…”
mentioning
confidence: 99%